2023
DOI: 10.3390/nano13030386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Refinement on the Comprehensive Mechanical Performance of W–Cu Composites

Abstract: W–Cu composites are commonly subjected to coupled multiple fields in service, which imposes high requirements on their overall performance. In this study, the ultrafine-grained W–Cu composite was fabricated using the combination of electroless plating and spark plasma sintering. The wear resistance and high-temperature compressive properties of the ultrafine-grained W–Cu composite were investigated and compared with those of the commercial coarse-grained counterpart. Moreover, the underlying strengthening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Existing processes for the preparation of copper-based contact materials include: induced copper powder fusion infiltration, pre-sintered tungsten skeleton fusion infiltration, activation sintering, high-temperature liquid-phase sintering, vacuum sintering, and injection molding sintering. The microstructures of CuW composites produced under different process conditions are very different, and their comprehensive properties are therefore significantly different [4][5][6][7].…”
Section: Preparation Process Of Cuw/graphene-enhanced Cuw Composites ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing processes for the preparation of copper-based contact materials include: induced copper powder fusion infiltration, pre-sintered tungsten skeleton fusion infiltration, activation sintering, high-temperature liquid-phase sintering, vacuum sintering, and injection molding sintering. The microstructures of CuW composites produced under different process conditions are very different, and their comprehensive properties are therefore significantly different [4][5][6][7].…”
Section: Preparation Process Of Cuw/graphene-enhanced Cuw Composites ...mentioning
confidence: 99%
“…Copper-tungsten (CuW) composites, as a prototypical two-phase pseudo-alloy, integrate the high conductivity and thermal conductivity of copper with the exceptional strength and arc ablation resistance of tungsten. Owing to these advantageous characteristics, CuW composites, especially CuW80 (80 wt.% W content), are extensively utilized as electrical contacts in high-voltage circuit breakers [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For W-Cu composites, the strengthening phase is mainly distributed in the grain boundary of W or W/Cu phase boundary, [149] and the strengthening effect is mainly achieved by the pinning [140] Copyright 2023, Open Access. 40.…”
Section: Distribution Of Dispersion Strengthening Phasementioning
confidence: 99%
“…[ 139 ] Han et al investigated the wear behavior and high‐temperature deformation behavior of the UFG W–Cu composite. [ 140 ] It was found that grain refinement enhanced the resistance against plastic deformation, leading to a reduced thickness of mechanical mixing layer and debris size in the UFG W–Cu composite. In addition, the high‐temperature strength of UFG W–Cu composite was largely improved due to the grain refinement and enhanced blocking effect of W phase on dislocations.…”
Section: Strengthening Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation